Physical and electrical properties of ceramic obtained from white rice husk ash and soda lime silica glass - Bateni, Nasim Heidari (2014)
Rice Husk (RH) is a biodegradable cheap waste product, which is available in more than 75 rice producing countries. RHs are treated as waste, causing pollution and disposal problems. Due to the environmental concern and the need to conserve energy and resources, a number of studies and researches have been addressed and confronted for the conversion of RH biomass into a high value-added and useful income-generating products. It is found that RH can be used as an excellent source to produce silicon-based materials, since it is known to have high silica ash in the range of 20-25%. Thermal combustion of RH at moderate temperature and heated in an air atmosphere produces the white rice husk ash (WRHA), which contains >90% of amorphous silica. Meanwhile, soda lime silica (SLS) glass is the most common type of glass. The commercially made glass bottle was used in this study as an urban waste. Mixing the SLS glass with WRHA may improve the physical and electrical properties. Therefore, in this present study, three different mixtures of WRHA and SLS glass consists of 97.5 wt.%, 95 wt.% and 92.5 wt.% of WRHA and 2.5 wt.%, 5 wt.% and 7.5 wt.% of SLS glass, respectively. These samples were sintered at difference temperatures of 900 °C, 1000 °C and 1200 °C and been labeled as S1, S2 and S3. Chemical, physical and electrical characteristics were analyzed using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), Archimedes’ method, ASTM C373, Scanning Electron Microscope (SEM), LCR meter and Sawyer-Tower circuit. XRF result shows that the main constituent of the mixture specimens is silica (91-94 wt.%) and impurities are such as CaO, K2O, SO3, Fe2O3. XRD result illustrates the crystalline structure of S1, S2 and S3. The physical analysis reveals that S3 shows better physical properties than other samples because it has the highest density (2.17 g/cm3), lowest porosity (22.4 %) and lowest LS (1.8 %). Electrical analysis shows that S1 (at 1200 °C) has the best electrical properties (εˊ = 11.1 and tan δ = 0.2 at 100 kHz) comparing with S2 and S3. The reason is that S1 has the lowest dielectric loss (0.26) and its P-E loop evaluation shows capacitor response. As a result, S1 is the best dielectric material among other ceramics.